Thermal degradation of (zinc-aluminium-layered double hydroxide-dioctyl sulphosuccinate) nanocomposite - Hussein, Mohd Zobir; Yun-Hin, Taufiq-Yap; Tawang, Mohd Maulana; Shahadan, Rodhyrolin (Elsevier Science, 2002)
Zinc-aluminium-layered double hydroxide containing dioctyl sulphosuccinate in the lamella for the formation of an organic-inorganic layered hybrid nanocomposite (ZALDIN) was synthesized by spontaneous self-assembly of organic and inorganic components from an aqueous phase. The heat-treated ZALDIN (ZALDITs) was obtained by heating ZALDIN at 150-800 °C under atmospheric pressure. The layered structure of the nanocomposite collapsed when the sample was heated at 150-250 °C. The formation of ZnO phase was observed when ZALDIN was heat-treated at 250 °C or higher, and in addition, a ZnS phase was also observed when the sample was heat-treated at 800 °C. The ZnO phase became more prominent as the heating temperature increased. The specific surface area for ZALDITs generally increased with temperature, with an optimum of about 62 m2/g at 600 °C. However, the surface area decreased to 39 m2/g at 800 °C, compared to 4 m2/g for ZALDIN.